Consumer Preferences on Sago (Metrixylon Sp) Burger Modification: Analysis of Organoleptic Characteristics and Recipe Standardization - Mahyiddin, Zuraini; Hamid, Yuli Heirina; Indani, Indani; Faudiah, Nurul; Mizan, Akbar (JURNAL PENDIDIKAN DAN KELUARGA, 2024)
Sago palm, a natural product sourced from Simeulue Island, where the majority of the population engages in farming and fishing, is facing a decline in the production of sago flour. To address this issue, the author sought to incorporate sago flour (Metroxylon Sp) into the creation of burger buns, dubbed "Sago Burger." The objectives of this study were to evaluate organoleptic characteristics, establish standard recipes, and analyze consumer preferences. Employing a quantitative research methodology, the study was conducted as an experiment, with five culinary lecturers serving as expert panelists and 30 consumer panelists, aged 18-25 years, participating. The data analysis technique used was a one-way ANOVA test, followed by the LSD test. Based on the organoleptic test results of the expert panelists, it was concluded that sago burgers containing 60 g (20%) of sago flour were the preferred option. Analysis of consumer data using one-way ANOVA revealed that Fcount < Ftable, leading to the rejection of H1 and acceptance of H0, as there was no significant impact of adding sago flour (Metroxylon sp.) on the organoleptic characteristics of sago burgers. Researchers who wish to build upon this study are advised to incorporate vegetable fat and continue to investigate the nutritional content of sago burgers (Metoxylon spp.).